Perencanaan Dan Simulasi Jaringan LTE ( Long Term Evolution ) Di kota Pekanbaru - Sari, Linna Oktaviana; Firmawan, Andes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The development of information and communication technologies growing more rapidly, as well as wireless communications technology. At the same time, theneed for information is also greater with the higher mobility. Technology Long Term Evolution (LTE) is believed to be able to answer that question.LTE is a technology developed by 3GPP as the development of mobile communication technology before. In theory LTE in this thesis is to make an LTE network simulation based methods duplex Frequency Division Duplex (FDD) with a frequency of 1800 MHz in the city of Pekanbaru using software Atoll. In this paper used the method of planning coverage to support the model propagated COST-231 hata are in use by means of simulation.The simulation results show Pekanbaru require at least 99 LTE site that is covered Ratio Signal (RS) and Carrier to Interference Noise Ratio (CINR) of at least 97%. The results of the simulation throughput, customers who successfully connected to the network at abandwidth of 5 MHz amounted to 82.7% and to a frequency of 10 MHz by 86.4%, while for a frequency of 15 MHz at 86.4%, and to a frequency of 20 MHz by 66%.Keywords: LTE, Atoll, Bandwidth, Coverage